The Fungal Metabolite (+)-Terrein Abrogates Ovariectomy-Induced Bone Loss and Receptor Activator of Nuclear Factor-κB Ligand–Induced Osteoclastogenesis by Suppressing Protein Kinase-C α/βII Phosphorylation - Sakaida, Kyosuke; Omori, Kazuhiro; Nakayama, Masaaki; Mandai, Hiroki; Nakagawa, Saki; Sako, Hidefumi; Kamei, Chiaki; Yamamoto, Satoshi; Kobayashi, Hiroya; Ishii, Satoki; Ono, Mitsuaki; Ibaragi, Soichiro; et al. (Frontiers in Pharmacology, 2021)
Osteoporosis is a common disease characterized by a systemic impairment of bone mass and microarchitecture that results in fragility fractures. Severe bone loss due to osteoporosis triggers pathological fractures and consequently decreases the daily life activity and quality of life. Therefore, prevention of osteoporosis has become an important issue to be addressed. We have reported that the fungal secondary metabolite (+)-terrein (TER), a natural compound derived from Aspergillus terreus, has shown receptor activator of nuclear factor-kappaB ligand (RANKL)-induced osteoclast differentiation by suppressing nuclear factor of activated T cells 1 (NFATc1) expression, a master regulator of osteoclastogenesis. TER has been shown to possess extensive biological and pharmacological benefits; however, its effects on bone metabolism remain unclear. In this study, we investigated the effects of TER on the femoral bone metabolism using a mouse ovariectomized osteoporosis model (OVX mice) and then on RANKL signal transduction using mouse bone marrow macrophages (mBMMs). In vivo administration of TER significantly improved bone density, bone mass, and trabecular number in OVX mice (p < 0.01). In addition, TER suppressed TRAP and cathepsin-K expression in the tissue sections of OVX mice (p < 0.01). In an in vitro study, TER suppressed RANKL-induced phosphorylation of PKCalpha/betaII, which is involved in the expression of NFATc1 (p < 0.05). PKC inhibitor, GF109203X, also inhibited RANKL-induced osteoclastogenesis in mBMMs as well as TER. In addition, TER suppressed the expression of osteoclastogenesis-related genes, Ocstamp, Dcstamp, Calcr, Atp6v0d2, Oscar, and Itgbeta3 (p < 0.01). These results provide promising evidence for the potential therapeutic application of TER as a novel treatment compound against osteoporosis.